2004
DOI: 10.1016/j.rapm.2003.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Interscalene perineural ropivacaine infusion:a comparison of two dosing regimens for postoperative analgesia

Abstract: Following moderately painful ambulatory shoulder surgery, decreasing an interscalene perineural ropivacaine 0.2% basal rate from 8 to 4 mL/h provides similar baseline analgesia and lengthens infusion duration, but compromises other infusion benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 27 publications
1
51
1
Order By: Relevance
“…Patients and their carers should be given extensive oral and written instructions about management, side effects and care of the local anaesthetic catheter, and have 24-hour a day telephone access to an anaesthesiologist during the postoperative period while CNPB is in use (Swenson et al, 2006), as 30% of patients make unscheduled phone calls regarding catheter infusions despite been given adequate written and verbal instructions Level II). A review of 620 outpatients with CPNB (including popliteal fossa, fascia iliaca and interscalene) showed that 4.2% required assistance by the anaesthesiologist after discharge from hospital for problems relating to issues such as patient education, inadequate analgesia and equipment malfunction; only one patient was unable to remove their catheter (Swenson et al, 2006 Level IV), although patients may have significant anxiety about catheter removal at home (Ilfeld et al, 2004 Level IV).…”
Section: Level Ii)mentioning
confidence: 99%
“…Patients and their carers should be given extensive oral and written instructions about management, side effects and care of the local anaesthetic catheter, and have 24-hour a day telephone access to an anaesthesiologist during the postoperative period while CNPB is in use (Swenson et al, 2006), as 30% of patients make unscheduled phone calls regarding catheter infusions despite been given adequate written and verbal instructions Level II). A review of 620 outpatients with CPNB (including popliteal fossa, fascia iliaca and interscalene) showed that 4.2% required assistance by the anaesthesiologist after discharge from hospital for problems relating to issues such as patient education, inadequate analgesia and equipment malfunction; only one patient was unable to remove their catheter (Swenson et al, 2006 Level IV), although patients may have significant anxiety about catheter removal at home (Ilfeld et al, 2004 Level IV).…”
Section: Level Ii)mentioning
confidence: 99%
“…CISB for shoulder surgery provides better analgesia than placebo or systemic opioids do and is associated with less opioid consumption and fewer opioid-related side effects. 184,[209][210][211][212][213] CISB with perineural infusion of local anesthetic has been shown to benefit patient rehabilitation 214 and can be continued at home with a portable infusion pump. 215 In a randomized controlled study, Ilfeld and colleagues 166 showed that ambulatory CISB with perineural infusion of 0.2% ropivacaine decreased the time until readiness for discharge after total shoulder arthroplasty by allowing good shoulder range of motion and providing adequate pain control without parenteral opioids.…”
Section: Interscalene Blockmentioning
confidence: 99%
“…One uses a stimulating catheter, which is described in greater detail elsewhere [49,50]. Here we describe a technique using a non-stimulating catheter.…”
Section: Needlementioning
confidence: 99%
“…For continuous infusion, bupivacaine 0.125%, levobupivacaine 0.125% or ropivacaine 0.2% may be used, with an infusion regimen of 8 ml/hr and 2 ml boluses once per hour [49]. The interested reader is referred to additional references for more detailed information on ambulatory catheters and local anesthetic infusion modes [49,52].…”
Section: Local Anesthetics and Additivesmentioning
confidence: 99%
See 1 more Smart Citation